From Michotte Until Today: Why the Dichotomous Classification of Modal and Amodal Completions Is Inadequate. (May 2019) - Scherzer, Tom R.; Faul, Franz
The distinction between modal and amodal completion is ubiquitous in the perception literature. It goes back to the seminal publication "Les compléments amodaux des structures perceptives" by A. Michotte, G. Thinès, and G. Crabbé (Publications Universitaires de Louvain: Louvain) in 1964. We review and discuss this work in this article and show commonalities and differences to today's view. We then argue that the dichotomous distinction between modal and amodal completions is problematic in phenomenological, empirical, logical, and theoretical terms. Finally, we propose alternative criteria allowing for a more differentiated classification scheme for completion phenomena. This scheme seems to be consistent with all known empirical findings and can also be generalized to nonvisual domains of perception.